Farm Animal Medicine and Surgery For Small Animal Veterinarians - Duncanson, Graham R (CABI, 2014)
The book aims to provide an easily accessible reference to the information required by practising veterinarians confronted by the emergency care of farm animals. Although information on the provision of emergency care is the prime aim of the book, information is also provided on likely surgical procedures (in the broadest possible sense) that will need to be carried out by clinicians in farm animal practice. Each chapter follows a similar format in consisting of a series of sections, often with subsections, generally with either a brief summary of or introduc- tion to the subject concerned, and with or without accompanying lists of the information rele- vant to that topic, be it equipment, medicines, disease signs, diagnosis and treatment, or surgical conditions and procedures. First, there are two general chapters on veterinary equipment and medicines, mostly con- sisting of practical checklists for use in an emergency. The rest of the book presents information on the medicine and surgery of farm animal species. Cattle, camelids and pigs are addressed in separate chapters, while sheep and goats are linked together in a single chapter, though highlighting the differences between the two. The chapter on domestic poultry is centred on chickens, but waterfowl, guinea fowl, peafowl and quails are referenced when relevant. The chapter on notifiable diseases near the end of the book is mainly for the UK and Europe, but other areas are included if thought to be of note. The author hopes this book will be useful for veterinary practitioners throughout the world who are treating farm animals. However, it has mainly been written for small animal practitioners who are asked to treat pet farm animals or who are asked by smallholders to treat their animals. The author also hopes that the book will be particularly useful for veterinary students and younger graduates. Veterinary science is evolving at an ever increasing rate and so some of the information presented here may be out of date before publication. The author apologizes for this and any inaccuracies. He hopes that these can be corrected in future editions and would be really grate- ful for any contact from readers via email to vetdunc@btinternet.com